2015
DOI: 10.1515/eces-2015-0039
|View full text |Cite
|
Sign up to set email alerts
|

Considerations of Impact of Venturi Effect on Mesophilic Digestion

Abstract: Hydrodynamic cavitation caused by the Venturi effect is one of the most promising methods of sewage sludge pre-treatment. This study has been carried out to investigate the effect of hydrodynamic cavitation on disintegration of activated sludge foam and mesophilic fermentation. Cavitation was generated in standard Venturi tube with the diameter ratio β = d0/d1 = 0.30, working at σ = 0.249. Detailed Computational Fluid Design (CFD) analysis in class of k-∈ model of internal flow has been presented. Obtained ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Hydrodynamic cavitation triggered by the Venturi effect is a promising process for pretreatment of waste activated sludge prior to mesophilic fermentation according to many authors, including Machnicka et al [113]. Furthermore, mesophilic digestion trials have reported a significant increase in the biogas production of approximately 36.1% and 62.16% for 10% and 30% of the volume of foam added to the digestion chamber, respectively.…”
Section: Physical Methodsmentioning
confidence: 99%
“…Hydrodynamic cavitation triggered by the Venturi effect is a promising process for pretreatment of waste activated sludge prior to mesophilic fermentation according to many authors, including Machnicka et al [113]. Furthermore, mesophilic digestion trials have reported a significant increase in the biogas production of approximately 36.1% and 62.16% for 10% and 30% of the volume of foam added to the digestion chamber, respectively.…”
Section: Physical Methodsmentioning
confidence: 99%
“…Thus, the entire productive volume of the reactor is used efficiently. Machnicka et al [53] showed how the addition of cavitationdisintegrated foam to mesophilic anaerobic digestion can improve the process and the production of biogas. The thermophilic digestion mode is more efficient in terms of biogas yield per unit time, but its use can be limited because of economic indicators of the cost of heating the substrate in the bioreactor, and it depends on external temperatures and thus on the climatic zone.…”
mentioning
confidence: 99%
“…One such possibility may be the use of disintegration methods. As we have shown in our earlier works (Grübel and Suschka 2015 ; Machnicka et al 2015 ; Suschka and Grübel 2016 ; Grübel and Machnicka 2020 ; Li et al 2021 ), the disintegration process effectively releases organic matter into the supernatant liquid of WAS, which contributes to the increased production of biogas. In connection with the above, we have undertaken research to determine the effectiveness of disintegration in removing selected bacterial indicators and parasite eggs.…”
Section: Resultsmentioning
confidence: 61%
“…Hydrodynamic disintegration of WAS was done with the use of a pressure pump (12 bar) equipped with a constructed cavitation nozzle (Grübel and Suschka 2015 ; Machnicka et al 2015 ). Pumping 25 l of WAS through the nozzle took 3 min.…”
Section: Methodsmentioning
confidence: 99%